Control processes and red tape in Philippine bureaucracy notes on administrative inefficiency - Bautista, Victoria A. (Philippine Journal of Public Administration, 1982)
While bureaucracy was conceived as the most rational form of organization characterized by precision, speed, and unambiguity, the realities of public organizations today present an inefficient organizational structure that relies heavily on established rules and regulations Formalized procedures in government, particularly in the implementation of control measures designed to prevent bureaucratic misbehavior, have brought with them other attendant problems commonly referred to as "red tape." As such, red tape is associated with some control measures of bureaucracy especially when bureaucrats pursue ritualistic adherence of the rules regardless of end goals and terminal values by which these rules have been created. In this sense, it becomes important to define the causes and effects of control measures, especially when they begin to serve as obstacles in the efficient performance of government functions Red tape must also be defined and clearly identified if bureaucracy is to surmount its challenge.